Embedding equity into school mental health theory: Introduction to Part 2 of the special issue series. Issue 12 (30th September 2022) - Gaias, Larissa; Jones, Janine; Exner‐Cortens, Deinera; Splett, Joni; Walker, Whitney
Abstract: In this article, we present an introduction to the second part of a two‐part special series focused on embedding equity into school mental health. In the previous part, we focused on measurement and practice, and in this second part, we focus on theory. Practitioner points: Explicitly addressing equity in school mental health research and practice is important for ensuring that services are accessible, appropriate, and effective for all students, especially those who face marginalization within schools. This special issue includes eight articles focused on integrating equity into school mental health theory. An appendix is also included outlining recommendations for research and practice compile across the two issues of the special series.